Myostatin Levels in SMA Following Disease‐Modifying Treatments: A Multi‐Center Study - Fiorella Piemonte; Sara Petrillo; Anna Capasso; Giorgia Coratti; Adele D'Amico; Michela Catteruccia; Maria Carmela Pera; Concetta Palermo; Marika Pane; Emanuela Abiusi; Gianpaolo Cicala; Marianna Villa; et al. (Annals of Clinical and Translational Neurology, 2025)
ABSTRACT Objective This study investigated myostatin levels in SMA patients receiving disease‐modifying therapies (DMTs) to understand their relationship with treatment duration and functional status. Methods Our study includes both cross‐sectional and longitudinal analyses of myostatin levels in treated SMA patients. The longitudinal cohort included 46 treatment‐naive patients assessed at baseline and 12 months post‐treatment. Myostatin levels were measured using ELISA. Age‐matched controls (n = 89) were included for comparison. The cross‐sectional study included 128 patients with variable durations of treatment (from 0.4 to 7.2 years). In both cohorts, myostatin levels were correlated with SMA type, functional status, and clinical outcomes. Results Baseline myostatin levels were significantly lower than controls (p < 0.001), except during the neonatal period in presymptomatic patients. After 12 months of treatment, there were no significant changes compared to baseline levels (p = 0.1652). The only substantial changes were observed in presymptomatic neonates, who showed a reduction of myostatin despite treatment intervention. There was a significant correlation between myostatin levels, functional status, and SMA type both in the cross‐sectional and longitudinal groups. Interpretation This study demonstrates lower myostatin levels in SMA patients compared to controls. The association between myostatin levels, functional status, and SMA type suggests its possible role as a disease severity biomarker. The utility of myostatin as a biomarker for DMT response remains controversial; while we observed no significant increase in myostatin levels following treatment, we also did not observe the progressive reduction previously reported in untreated patients.